High spatial resolution and temporally resolved T2* mapping of normal human myocardium at 7.0 Tesla: an ultrahigh field magnetic resonance feasibility study. - Fabian Hezel; Christof Thalhammer; Sonia Waiczies; Jeanette Schulz-Menger; Thoralf Niendorf (PLoS ONE)
Myocardial tissue characterization using T(2)(*) relaxation mapping techniques is an emerging application of (pre)clinical cardiovascular magnetic resonance imaging. The increase in microscopic susceptibility at higher magnetic field strengths renders myocardial T(2)(*) mapping at ultrahigh magnetic fields conceptually appealing. This work demonstrates the feasibility of myocardial T(2)(*) imaging at 7.0 T and examines the applicability of temporally-resolved and high spatial resolution myocardial T(2)(*) mapping. In phantom experiments single cardiac phase and dynamic (CINE) gradient echo imaging techniques provided similar T(2)(*) maps. In vivo studies showed that the peak-to-peak B(0) difference following volume selective shimming was reduced to approximately 80 Hz for the four chamber view and mid-ventricular short axis view of the heart and to 65 Hz for the left ventricle. No severe susceptibility artifacts were detected in the septum and in the lateral wall for T(2)(*) weighting ranging from TE = 2.04 ms to TE = 10.2 ms. For TE >7 ms, a susceptibility weighting induced signal void was observed within the anterior and inferior myocardial segments. The longest T(2)(*) values were found for anterior (T(2)(*) = 14.0 ms), anteroseptal (T(2)(*) = 17.2 ms) and inferoseptal (T(2)(*) = 16.5 ms) myocardial segments. Shorter T(2)(*) values were observed for inferior (T(2)(*) = 10.6 ms) and inferolateral (T(2)(*) = 11.4 ms) segments. A significant difference (p = 0.002) in T(2)(*) values was observed between end-diastole and end-systole with T(2)(*) changes of up to approximately 27% over the cardiac cycle which were pronounced in the septum. To conclude, these results underscore the challenges of myocardial T(2)(*) mapping at 7.0 T but demonstrate that these issues can be offset by using tailored shimming techniques and dedicated acquisition schemes.